Asymptotic growth bounds for the 3‐D Vlasov‐Poisson system with point charges. (21st February 2018) - Li, Donghao; Zhang, Xianwen
Abstract : In this article, we consider the asymptotic behavior of the classical solution to the 3‐dimensional Vlasov‐Poisson plasma interacting repulsively with N point charges. The large time behavior in terms of diameters of its velocity‐spatial supports is improved to O ( t 2/3+ ϵ ) for any ϵ >0.